2020
DOI: 10.3390/educsci10030064
|View full text |Cite
|
Sign up to set email alerts
|

Inspiring a Self-Reliant Learning Culture while Brewing the Next Silicon Valley in North Wales

Abstract: Practical strategies for improving individual engagement and performance within an engineering team project learning environment were applied and evaluated. While methodological refinements were required due to the structural challenges and novelty of the practice, positive outcomes such as a perceived increase in engagement and technical proficiency were recorded. Critical aspects in the current approach are the well-known issue of assessing individual contributions within group performance, and setting a pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…Therefore, it is argued that a clear documentation of the thinking processes can be used to prevent these issues. This can also help prevent "freeloading" behavior, which creates a negative learning environment and assesment issues for student teams [46].…”
Section: B Instructional Practicesmentioning
confidence: 99%
“…Therefore, it is argued that a clear documentation of the thinking processes can be used to prevent these issues. This can also help prevent "freeloading" behavior, which creates a negative learning environment and assesment issues for student teams [46].…”
Section: B Instructional Practicesmentioning
confidence: 99%
“…This constituted the 'summative peer assessment' step of the TBL model (see Figure 1). Although the use of Web-PA is not common in the engineering education literature, it has demonstrated to be a reliable instrument to measure the contribution of individual students in teamwork activities (Stevenson, Seenan et al 2012, Palego andPierce 2020). The use of peer-assessment has been deeply discussed by Planas-Llado et al, who found that teams that viewed their team as functioning best distributed equal scores among their teammates in peerassessment exercises (Planas-Lladó, Feliu et al 2020).…”
Section: Data Collectionmentioning
confidence: 99%
“…While the emergence of Brainport-Eindhoven as a deeptech ecosystem has not gone unnoticed [2,[8][9][10], a clear account of how and why this region arose as a globally leading hotspot is not yet available. Such a descriptive account would be valuable because the Eindhoven region's setting and history appear to be fundamentally different from those of Silicon Valley, the global benchmark for developing technology-driven ecosystems [11][12][13]. As such, the Eindhoven region has the potential to provide the archetype of a collaborative ecosystem, one that may provide an alternative to the "winner-takes-all" entrepreneurial culture of Silicon Valley [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the three structural conditions previously outlined appear to be highly complementary in supporting and enhancing the collaborative ecosystems needed for deeptech value propositions. These conditions also turn the Eindhoven case into an interesting benchmark, one that is fundamentally different from Silicon Valley, the global benchmark for technology-driven ecosystems [11][12][13]. As such, the Eindhoven region has the potential to provide the archetype of a collaborative ecosystem, as an alternative to the "winner-takes-all" and short-cycled entrepreneurial culture of Silicon Valley [14,15].…”
mentioning
confidence: 99%